1979
DOI: 10.1161/01.str.10.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic control of cerebral blood flow and energy metabolism in the rat.

Abstract: EVIDENCE NOW EXISTS that there are at least 2 types of adrenergic innervation of cerebral vessels, one from the cervical sympathetic plexus innervating mainly extracerebral arteries, but also reaching cerebral arterioles of 15 n diameter 1 ' 2 and the other originating in the locus ceruleus and impinging directly on the walls of intramedullary arterioles. 36The influences of these vascular neurogenic systems on cerebral circulatory physiology or metabolism are still not understood.Results of recent physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…1 h before the assay) reduced the calculated rate of high energy use by ~ 50% based on postmortem changes in rat brain energy metabolite levels, whereas the non‐specific α‐blocker, phenoxybenzamine had no effect (Kogure et al . ). A still‐lower propranolol dose (2.5 mg/kg, i.v.)…”
Section: Regulation Of Aerobic Glycolysis Via Adrenergic Receptorsmentioning
confidence: 97%
“…1 h before the assay) reduced the calculated rate of high energy use by ~ 50% based on postmortem changes in rat brain energy metabolite levels, whereas the non‐specific α‐blocker, phenoxybenzamine had no effect (Kogure et al . ). A still‐lower propranolol dose (2.5 mg/kg, i.v.)…”
Section: Regulation Of Aerobic Glycolysis Via Adrenergic Receptorsmentioning
confidence: 97%
“…Astrocytes are known targets of the locus coeruleus, and they have ␣ 1 -, ␣ 2 -, ␤ 1 -and ␤ 2 -adrenergic receptors linked to different second messenger and signaling pathways that modulate their glucose transport, glycolysis, oxidative metabolism, glycogen synthesis and degradation, glutamate uptake, glutamine hydrolysis, and other activities; in general, these processes are stimulated in cultured astrocytes by receptor agonists, with the specific effects dependent on receptor subtypes and signaling pathways [29,32,33,50,51]. Noradrenergic pathway intervention can cause either a rise or fall in brain glucose utilization in animals, depending on condition (with or without stimulation), brain region, and the agonists or antagonists used to target adrenoceptor subtypes [36,38,40,59,60]. Stimulation of glycogenolysis by noradrenaline has a profound effect because even a severe energy crisis does not overwhelm its regulatory contributions; during ischemia and seizures more glycogen remains in the ipsilateral cerebral cortex after unilateral lesion of the locus coeruleus [27,35].…”
Section: Adrenergic Modulation Of Oci and Metabolismmentioning
confidence: 99%
“…In regard to CMRo,, it has been suggested that catecholamines increase CMRo, by direct stimulation of metabolism as is seen in peripheral tissue (Himms-Hagen, 1967). Kogure et al (1979) reported that administration of reserpine (to deplete central monoamines) or propanolol (to block central p receptors) reduced the rate of high-energy phosphate depletion following decapitation in cervical sympathetic ganglionectomized rats whereas denervation alone had no effect. These results were interpreted to suggest that central adrenergic neurons influence CMRo, by acting on p receptor sites on the cell membrane.…”
Section: Number Of Sectionsmentioning
confidence: 99%